Solid‐to‐Hollow Conversion of Silver Nanocrystals by Surface‐Protected Etching. Issue 71 (21st November 2018) - Liu, Kai; Liu, Hongpo; Fan, Qikui; Zhang, Shumeng; Liu, Zhaojun; Han, Lu; Li, Houshen; Gao, Chuanbo
Abstract: Although hollow silver nanocrystals possess unique plasmonic properties, there is a lack of robust strategies to synthesize such nanocrystals with high efficiency and controllability. To solve this problem, a new surface‐protected etching strategy to convert solid Ag nanocrystals, which are widely available from conventional syntheses, into their hollow counterparts, producing a family of hollow Ag nanocrystals is reported. Hollow Ag nanospheres and nanotubes were prepared conveniently in this way. The key was the surface modification of Ag nanocrystals by a minor amount of Pt prior to a controllable etching process, which accounts for enhanced stability of the Ag surface and subsequent etching of Ag from the inner part of the nanocrystals while retaining the overall crystal morphology. These hollow Ag nanocrystals showed distinctive optical properties, as demonstrated by the enhanced optical transmittance of flexible electrodes fabricated with Ag nanotubes, compared to nanowires. These hollow Ag nanocrystals hold promise in different plasmonic and electronic applications. Abstract : Hollow silver nanospheres and nanotubes were synthesized by surface‐protected etching of their solid counterparts and showed distinctive optical properties.